(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The purpose of the work is to identify the essence of personnel management risk, with a focus on its components and their impact on enterprise development goals. Risk arises from conducting business in conditions of uncertainty. It has been established that risks in personnel management are difficult to identify and assess, as they are associated with human resources, which are based on personal essence. Hence, two problems arise. Firstly, risk increases the complexity of evaluating the consequences of decisions made. Secondly, risk in personnel management at the conceptual level affects potential effectiveness. Therefore, it is more appropriate to use the term "uncertainty" in personnel management instead of the concept of risk. A person making decisions regarding human resource management in conditions of wartime economy deals with uncertainty, not risk. It is proven that uncertainty and risk are functions of such factors as the quantity and quality of information available to management personnel, and the variability of conditions for implementing personnel decisions. Two main approaches to defining the determinants of decision-making success by managers are distinguished. The first relates to factors influencing task execution, and the second to personal factors. It is argued that in the field of human resource management, the level of risk depends on the subjective perception of risk by personnel. Considering the attitude toward risk of the decision-maker, three main types of behavior are identified: risk-prone, risk-averse, and risk-neutral. Identifying the purpose of personnel activity is related to the formation of enterprise development strategy and the development of prospective human resource management plans. The purpose directs the will of the employee and determines the future outcome. Personal (individual) goals are defined in the form of a postulate or model. The purpose of HR activity based on both traditional and modern human resource management models is identified. Managers in conditions of wartime economy make decisions based on external data over which they have limited control. Therefore, their attention should be focused on an environment unfavorable for making personnel decisions.